The broken tower - Braffet, Kelly, 1976- (Braffet, Kelly, 1976- Barrier Lands, 2022)
Judah the Foundling chose freedom over betrayal when she leaped from the top of the castle tower. Now she finds herself wandering an unknown forest, far from everything and everyone she loves. For the first time in her life, she's beyond the great Wall that surrounds Highfall castle; for the first time, she's alone. Away from the Seneschal, the power behind the throne; away from Nate Clare, the House Magus who was her teacher, friend, betrayer. Away from her foster brother, Gavin, with whom she has a mysterious bond that has kept them together--and kept her alive. But Judah isn't free. Fiercely sought by those who believe she holds the key to unlocking the power trapped in the world, she must learn to navigate the dangers of an unfamiliar place. She knows that somewhere, Gavin is in peril. To save him, she not only must learn to use the new power she discovers inside herself, she must survive.